Answer:
The answer is below
Step-by-step explanation:
Given that:
x(t) = at – bt2+c
a) x(t) = at – bt2+c
Substituting a = 1.4 m/s, b = 0.06 m/s2 and c =50 m gives:
x(t) = 1.4t - 0.06t² + 50
At t = 5, x(5) = 1.4(5) - 0.06(5)² + 50 = 55.5 m
At t = 0, x(0) = 1.4(0) - 0.06(0)² + 50 = 50 m
The average velocity (v) is given as:
![v=(x(5)-x(0))/(5-0)\\ \\v=(55.5-50)/(5-0)=1.1\\ \\v=1.1\ m/s](https://img.qammunity.org/2021/formulas/physics/high-school/7flvges5zqsa7l47yditej81uugldv79lb.png)
b) x(t) = 1.4t - 0.06t² + 50
At t = 10, x(10) = 1.4(10) - 0.06(10)² + 50 = 58 m
At t = 0, x(0) = 1.4(0) - 0.06(0)² + 50 = 50 m
The average velocity (v) is given as:
![v=(x(10)-x(0))/(10-0)\\ \\v=(58-50)/(10-0)=0.8\\ \\v=0.8\ m/s](https://img.qammunity.org/2021/formulas/physics/high-school/qr9g4uwy3bf5a98o3ygts8g5hjhxjec4xf.png)
c) x(t) = 1.4t - 0.06t² + 50
At t = 15, x(5) = 1.4(15) - 0.06(15)² + 50 = 57.5 m
At t = 10, x(10) = 1.4(10) - 0.06(10)² + 50 = 58 m
The average velocity (v) is given as:
![v=(x(15)-x(10))/(15-10)\\ \\v=(57.5-58)/(15-10)=0.1\\ \\v=0.1\ m/s](https://img.qammunity.org/2021/formulas/physics/high-school/4544t5yp9gtbwdz3tis344lqwd5a9ziwkd.png)